Does early‐life family income influence later dental pain experience? A prospective 14‐year study. (6th July 2017) - Ghorbani, Z; Peres, MA; Liu, P; Mejia, GC; Armfield, JM; Peres, KG
Abstract: Background: The aim of this study was to investigate the association between early‐life family income and dental pain experience from childhood to early adulthood. Methods: Data came from a 14‐year prospective study (1991/1992–2005/2006) carried out in South Australia, which included children and adolescents aged 4–17 years (N = 9875) at baseline. The outcome was dental pain experience obtained at baseline, 14 years later in adulthood and at a middle point of time. The main explanatory variable was early‐life family income collected at baseline. Results: The prevalence of dental pain was 22.8% at baseline, 19.3% at 'middle time' and 39.3% at follow up. The proportion of people classified as 'poor' at baseline was 27.7%. Being poor early in life was significantly associated with dental pain at 14‐year follow up (odds ratio = 1.45; 95% confidence interval = 1.27–1.66). Conclusions: Early‐life relative poverty is associated with more frequent dental pain across the 14‐year follow up and may be a key exposure variable for later dental conditions.